2019
DOI: 10.1111/jan.14109
|View full text |Cite
|
Sign up to set email alerts
|

Does improved postgraduate capacity shift the balance of power for nurse specialists in a low‐income country: A mixed methods study

Abstract: Aim To explore nurse specialists’ experiences of change and influence on practice two years after graduating with a postgraduate degree. Background In the absence of further study opportunities for nurses in their own country, a master's degree was introduced to train the first group of nurse specialists in Mozambique. Design Within a hybrid evaluation framework an exploratory, sequential mixed methods design was followed. Methods Qualitative data from focus group interviews with nurse specialists (N = 12) led… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Collin et al found in his study that the “majority of countries identified the need for specialist training for nurses in tuberculosis patient care (56.7%)” [ 27 ]. Authors of a recent study concluded that “Advanced knowledge is a clear source of power for SNs in this context and in a facilitative work environment, the impact of this knowledge could become much more tangible than what their current experience shows” [ 28 ]. Other positive findings are in a paper by Coen and Curry: “The comprehensive and dynamic nature of the CNS’ (clinical nurse specialist) practice allows application of multiple roles across various care settings [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collin et al found in his study that the “majority of countries identified the need for specialist training for nurses in tuberculosis patient care (56.7%)” [ 27 ]. Authors of a recent study concluded that “Advanced knowledge is a clear source of power for SNs in this context and in a facilitative work environment, the impact of this knowledge could become much more tangible than what their current experience shows” [ 28 ]. Other positive findings are in a paper by Coen and Curry: “The comprehensive and dynamic nature of the CNS’ (clinical nurse specialist) practice allows application of multiple roles across various care settings [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Continuance commitment to a minimum score of (3.06 ± 0.49) points, due to the higher nursing graduate student's career goals and career expectations, despite their signi cant knowledge and ideas are full of con dence, while in the clinical work their professional advantage and value can't give full play. Also they may affected by various in uences, and hard to overcome these di culties, in addition their clinical practice are limited, which lead them to produce career frustration and dissatisfaction and even thoughts of transition and resignation [18][19]. A study of South Korea con rmed that an awareness of the nursing profession does not guarantee full-time employment.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the research ability of postgraduate nursing students is uneven (Liao et al, 2015;Wang et al, 2017). In addition, interest of postgraduate nursing students in pursuing scientific careers has declined markedly (Bruce et al, 2019;Chang & Ramnanan, 2015). It is urgent to know what motivates or discourages postgraduate nursing students in their consideration for conducting research in order to prevent their research ability declining (Li et al, 2019;Ommering et al, 2018;Ommering et al, 2020).…”
mentioning
confidence: 99%
“…nursing students are the key trainees in nursing education (Bruce et al, 2019;Yan et al, 2019). Their research ability has a direct impact on the development of nursing.…”
mentioning
confidence: 99%